Mengenal Qira-at Al-Qur an Sya ban Muhammad Ismail; penerjemah HS. Agil Husin Al-Munawar, Abd Rahman Umar, H. Nasrulloh Jamaluddin - ISMAIL, Sya ban Muhammad; Al-Munawar, H.S. Agil Husin; Umar, Abd Rahman; Jamaluddin, H.Nasrullah (Dina Utama, 1993)
173 hlm. ; 21 cm.